Ezrin deficiency triggers glial fibrillary acidic protein upregulation and a distinct reactive astrocyte phenotype. Issue 12 (5th August 2022) - Schacke, Stephan; Kirkpatrick, Joanna; Stocksdale, Amy; Bauer, Reinhard; Hagel, Christian; Riecken, Lars Björn; Morrison, Helen
Abstract: Astrocytes are increasingly being recognized as contributors to physiological brain function and behavior. Astrocytes engage in glia‐synaptic interactions through peripheral astrocyte processes, thus modulating synaptic signaling, for example, by handling glutamate removal from the synaptic cleft and (re)provision to axonal terminals. Peripheral astrocyte processes are ultrafine membrane protrusions rich in the membrane‐to‐actin cytoskeleton linker Ezrin, an essential component of in vitro filopodia formation and in vivo peripheral astrocyte process motility. Consequently, it has been postulated that Ezrin significantly contributes to neurodevelopment as well as astrocyte functions within the adult brain. However, while Ezrin has been studied in vitro within cultured primary astrocytes, in vivo studies on the role of Ezrin in astrocytes remain to be conducted and consequences of its depletion to be studied. Here, we investigated consequences of Ezrin deletion in the mouse brain starting from early neuronal specification. While Ezrin knockout did not impact prenatal cerebral cortex development, behavioral phenotyping depicted reduced exploratory behavior. Starting with postnatal appearance of glia cells, Ezrin was verified to remain predominantly expressed in astrocytes. Proteome analysis of Ezrin deficient astrocytes revealed alterations in glutamate and ion homeostasis, metabolism and cell morphology – important processes for synaptic signal transmission. Notably, Ezrin deletion in astrocytes provoked (GFAP) glial fibrillary acidic protein upregulation – a marker of astrocyte activation and reactive astrogliosis. However, this spontaneous, reactive astrogliosis exhibited proteome changes distinct from ischemic‐induced reactive astrogliosis. Moreover, in experimental ischemic stroke, Ezrin knockout mice displayed reduced infarct volume, indicating a protective effect of the Ezrin deletion‐induced changes and astrogliosis. Main Points: Ezrin deficiency does not interfere with brain development. Ezrin loss provokes astrocytic GFAP upregulation. Ezrin knockout mice display altered explorative behavior in new environments and reduced stroke infarct spreading in experimental stroke model.